The Role of Non-Indigenous Papuan Teachers in Understanding Literacy in Cultural Diversity for Identity, Power and Social Justice of Indigenous Papuan Students in Senior High School - Sastri Br Rajaguk-guk; Ilza Mayumi; Liliana Muliastuti (Green Publisher Indonesia, 2025)
Papua, with its cultural and linguistic diversity, faces unique challenges in the field of education, particularly at the senior high school level. This study aims to analyze the role of non-Papuan teachers or migrant teachers in understanding literacy, cultural diversity, and its impact on the identity, power dynamics, and social justice of local Papuan students. The findings indicate that the obstacles faced by teachers include a lack of understanding of local culture, language differences, and minimal institutional support. As a result, many local Papuan students feel alienated, less motivated, and marginalized in the learning process. Migrant teachers have the potential to play a crucial role in creating an inclusive educational environment by employing culturally responsive pedagogical approaches. Collaborating with local communities and developing curricula that reflect local values can enhance the sense of belonging and engagement among local students. With strengthened ongoing professional training, teachers can be more effective in addressing cultural diversity and promoting social justice in the classroom. This research recommends the development of culturally-based curricula, intensive teacher training, and the use of technology as tools to bridge cultural gaps. These steps are expected to create a more inclusive education system, empower local Papuan students, and improve the quality of education in the region.